2015
DOI: 10.3233/wor-131721
|View full text |Cite
|
Sign up to set email alerts
|

An ergonomic approach for designing indian traditional vegetable cutter

Abstract: BACKGROUND: In India varieties of hand tools have been used to cut the vegetables. Traditional vegetable cutter is a commonly used hand tool which has been used for years in the kitchen. The tool may have some design related problems. The present study was undertaken to reduce those problems. OBJECTIVE: The study objective was to evaluate a new design of traditional vegetable cutters for use in the Indian kitchen. PARTICIPANTS: One hundred and fifty Indian women who regularly used a vegetable cutter for cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was also revealed that age was associated with pain in upper back, wrists/hands, fingers and elbows/forearms. It is observed that as a result of upgrading the activity (especially cutting and weeding) by designing new interventions may help for preventing MSDs among farmers in the near future 15 ) . The results dictates for the need to consider other physical and psychosocial factors of manual harvesting farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also revealed that age was associated with pain in upper back, wrists/hands, fingers and elbows/forearms. It is observed that as a result of upgrading the activity (especially cutting and weeding) by designing new interventions may help for preventing MSDs among farmers in the near future 15 ) . The results dictates for the need to consider other physical and psychosocial factors of manual harvesting farmers.…”
Section: Discussionmentioning
confidence: 99%
“…MSDs, particularly in the trunk, shoulders, and hands/wrists are progressively frequent in Asian producers 10 , 11 , 12 , 13 , 14 , 15 ) . In India, various studies 10 , 11 , 12 , 15 ) have reported MSDs in farmers and work related upper limb disorders occurrence rates for farmers reported at about 63–98%. To date there is limited study available on the prevalence of MSDs and their contributing risk factors for manual harvesting farmers.…”
Section: Introductionmentioning
confidence: 99%
“…The aging of the rural regions and the decrease in the farming population per household has led to a severe reduction in the labor force and an increase in labor intensity, causing serious WMSDs problems for farmworkers [ 4 , 5 ]. The prevalence of WMSDs, particularly in the trunk, shoulder, and hand/wrist, is very high in Asian farmers [ 6 , 7 , 8 , 9 ]. The prevalence (61.5%) of WMSDs among farmworkers, forestry workers, and fishers was 2.5 times higher than that (25.1%) of workers in other fields [ 10 ].…”
Section: Introductionmentioning
confidence: 99%